2018
DOI: 10.1007/s00181-018-1511-y
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence and economic sophistication

Abstract: Backed by strong empirical results, obtained from several different specification and sensitivity analyses, this paper contends that countries with high-intellectual quotient populations produce and export more sophisticated/complex products. This result is further reinforced by the quality of democracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 55 publications
(48 reference statements)
2
45
1
Order By: Relevance
“…In this section we model the hypothesis to be tested building on a model similar to the one developed by Lapatinas and Litina [ 26 ], considering elements derived from standard models of fiscal policy and growth. To study the relationship between fiscal policy and product-sophistication, we first construct the measure of economic sophistication ( EXPY ) using the framework developed by Hausmann et al [ 15 ].…”
Section: Fiscal Policy As a Determinant Of Economic Complexitymentioning
confidence: 99%
“…In this section we model the hypothesis to be tested building on a model similar to the one developed by Lapatinas and Litina [ 26 ], considering elements derived from standard models of fiscal policy and growth. To study the relationship between fiscal policy and product-sophistication, we first construct the measure of economic sophistication ( EXPY ) using the framework developed by Hausmann et al [ 15 ].…”
Section: Fiscal Policy As a Determinant Of Economic Complexitymentioning
confidence: 99%
“…Sepehrdoust et al (2019) have reported that trade policy liberalization is conducive to greater economic complexity. However, in their analyses that have used trade openness as a control variable, Lapatinas (2019) and Lapatinas and Litina (2019) have not found a signi cant effect of trade openness on economic sophistication.…”
Section: Model Speci Cationmentioning
confidence: 95%
“…[13] Note that we have used the population density variable in replacement with the population size variable (which has been used in the studies on the determinants of export diversi cation), so as to capture more precisely both the geographic potential of countries and the size of labour (e.g., Chu, 2019;Lapatinas and Litina, 2019). We have obtained that results do not change qualitatively and quantitatively.…”
Section: Econometric Approach and Conduct Of The Empirical Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, [56] have recently shown that countries exporting complex products tend to be more inclusive and have lower levels of income inequality than countries exporting simpler products. In addition, [57] find that countries with high intellectual quotient (IQ) populations produce and export more sophisticated/complex products, while [58] shows that the Internet has a positive effect on economic complexity. Adopting the economic complexity methodology, [59] compute a knowledge complexity index with more than two million patent records for US metropolitan areas between 1975-2010.…”
Section: Introductionmentioning
confidence: 99%